Use of food and spatial resources by two frogs of the genus Dendropsophus (anura: Hylidae) from La Selva, Costa Rica - Jiménez, Randall (2012)
Differences in the use of resources by similar species have been related to a reduction in the interspecific competition that allows coexistence. Also, other factors, such as high availability of resources in the environment, vegetation structure, environmental heterogeneity, reproductive modes, and predation, can influence the use of resources and favor coexistence. We studied the use of space and food resources by males of two species of hylid frogs, Dendropsophus ebraccatus and D. phlebodes, in two swamps in the Neotropical lowland forest at La Selva Biological Station, Costa Rica. We determined space and food use by characterizing calling sites and the diet of the frogs by stomach flushing. Males call from different substrates, and use different sizes of leaves and perch heights. Both species seem to be feeding generalists. Their diets are similar and indicate a moderate trophic niche overlap based on the type of prey consumed. Many males of both species had empty stomachs, suggesting that food resources are not an important factor affecting the coexistence of these species. Our study also indicates a lack of competitive interactions for space and food resources, and suggests that the abundant and structurally diverse vegetation provides many different vocalization sites for the male frogs and fosters coexistence of these species during the breeding season at La Selva.